Development of Extraintestinal Manifestations in Pediatric Patients with Inflammatory Bowel Disease - Heyman, Melvin B. (2009)
BACKGROUND: Extraintestinal manifestations (EIMs) in pediatric patients with inflammatory bowel disease (IBD) are poorly characterized. We examined the prevalence of EIMs at diagnosis, subsequent incidence, and risk factors for EIMs. METHODS: Data for 1649 patients from the PediIBD Consortium Registry, diagnosed with IBD before 18 years of age [1007(61%) with Crohn’s disease, 471(29%) with ulcerative colitis, and 171(10%) with indeterminate colitis], were analyzed using logistic regression, Kaplan-Meier, log rank tests and Cox models. RESULTS: EIMs were reported prior to IBD diagnosis in 97 of 1649 patients (6%). Older children at diagnosis had higher rates compared with younger children, and arthritis (26%) and aphthous stomatitis (21%) were most common. Among the 1552 patients without EIM at diagnosis, 290 developed at least one EIM. Kaplan-Meier estimates of cumulative incidence were 9% at 1 year, 19% at 5 years, and 29% at 15 years after diagnosis. Incidence did not differ by IBD type (p=0.20), age at diagnosis (p=0.22), or race/ethnicity (p=0.24). Arthritis (17%) and osteopenia/osteoporosis (15%) were the most common EIMs after IBD diagnosis. CONCLUSIONS: In our large cohort of pediatric IBD patients, 6% had at least one EIM before diagnosis of IBD. At least one EIM will develop in 29% within 15 years of diagnosis. Incidence of EIMs both before and after diagnosis of IBD differs by type of EIM and may be slightly higher in girls, but is independent of the type of IBD, age at diagnosis, and race/ethnicity.